2019
DOI: 10.1002/masy.201800052
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Oregano Essential Oil Microcapsules in Starch‐Poly (Butylene Adipate Co‐Terephthalate) (PBAT) Films

Abstract: Summary Cassava starch and poly(butylene adipate‐co‐terephthalate) (PBAT) based films containing microencapsulated oregano essential oil (OEO) and free OEO are produced by blow extrusion. Microcapsules produced by ionic gelation were characterized with respect to average size, morphology, and encapsulation efficiency. The microcapsules were spherical and ranged in size from 20 to 1000 μm. Encapsulation efficiency (EE) is 83%. The films are analyzed in terms of their morphology, mechanical properties, water vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The thickness of the thyme oil increased by 3.08 folds (113.33 µm of PLA/PBAT-Thyme 10% ) with respect to the control PLA/PBAT film (36.71 µm) while, the thickness of the clove oil composite film increased by 2.90 folds (106.67 µm of PLA/PBAT-Clove 10% ) depicting significant difference in the values ( Table 3 and Table 4 ). Similar results are seen in studies where the thickness increased with the incorporation of essential oil in the active packaging film [ 37 , 38 ]. This could be due to the distribution pattern of the essential oil in the matrix of the film.…”
Section: Resultssupporting
confidence: 86%
“…The thickness of the thyme oil increased by 3.08 folds (113.33 µm of PLA/PBAT-Thyme 10% ) with respect to the control PLA/PBAT film (36.71 µm) while, the thickness of the clove oil composite film increased by 2.90 folds (106.67 µm of PLA/PBAT-Clove 10% ) depicting significant difference in the values ( Table 3 and Table 4 ). Similar results are seen in studies where the thickness increased with the incorporation of essential oil in the active packaging film [ 37 , 38 ]. This could be due to the distribution pattern of the essential oil in the matrix of the film.…”
Section: Resultssupporting
confidence: 86%
“…According to Medeiros et al [21], the efficiency of the films in acting as active packaging is influenced not only by the concentration of oil, but also by the diffusion of the bioactive compounds into the medium, which in return depend on the interactions between the components, as well as their disposition inside the film. Microencapsulation of bioactive compounds is a technology that allows isolating and preserving compounds from inactivation by external agents [30].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The incorporation of essential oil into films is usually carried out by the emulsion between the oil and other components of the filmogenic solution, with the aid of a homogenizer [19] and the use, or not, of stabilizing agents [20], or encapsulated oil [21]. However, the incorporation of essential oils can affect the structural, barrier, mechanical, and optical properties of films [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the use of pinhão starch for film production (Daudt et al, 2014;Luchese, Frick, Patzer, Spada, & Tessaro, 2015). The blending of starch with other synthetic biodegradable polymers represents an important route to overcome the shortcomings of starch-based materials,such as poor water vapor barrier and their mechanical properties (de Medeiros et al, 2019). PBAT is a compostable polymer produced from fossil basis formed by the reaction of butanediol with adipic and terephthalic acid that display similar mechanical properties as low-density polyethylene (LPDE) (30 MPa as tensile strength and 700 as elongation at break).…”
Section: Food Engineering Materials Science and Nanotechnologymentioning
confidence: 99%